2017
DOI: 10.1155/2017/6347138
|View full text |Cite
|
Sign up to set email alerts
|

The CECARI Study: Everolimus (Certican®) Initiation and Calcineurin Inhibitor Withdrawal in Maintenance Heart Transplant Recipients with Renal Insufficiency: A Multicenter, Randomized Trial

Abstract: In this 3-year, open-label, multicenter study, 57 maintenance heart transplant recipients (>1 year after transplant) with renal insufficiency (eGFR 30–60 mL/min/1.73 m2) were randomized to start everolimus with CNI withdrawal (N = 29) or continue their current CNI-based immunosuppression (N = 28). The primary endpoint, change in measured glomerular filtration rate (mGFR) from baseline to year 3, did not differ significantly between both groups (+7.0 mL/min in the everolimus group versus +1.9 mL/min in the CNI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…During follow-up, maintenance immunosuppression was switched to a CNI plus everolimus in 20 patients with severe CAV, at a median of 7.1 years (range, 1.0 -16.1) post-HTx. In addition, 39 patients without severe CAV received everolimus: because of renal insufficiency in 18 (most in a CNIfree regimen as part of a clinical study (19)), intolerance for MMF in 10, skin cancer in 6 and miscellaneous reasons in 5. By the end of the first postoperative year, 12% of patients had experienced at least one episode of treated acute rejection (acute cellular rejection in 57 patients and antibody-mediated rejection in 5 patients).…”
Section: Patients' Characteristicsmentioning
confidence: 99%
“…During follow-up, maintenance immunosuppression was switched to a CNI plus everolimus in 20 patients with severe CAV, at a median of 7.1 years (range, 1.0 -16.1) post-HTx. In addition, 39 patients without severe CAV received everolimus: because of renal insufficiency in 18 (most in a CNIfree regimen as part of a clinical study (19)), intolerance for MMF in 10, skin cancer in 6 and miscellaneous reasons in 5. By the end of the first postoperative year, 12% of patients had experienced at least one episode of treated acute rejection (acute cellular rejection in 57 patients and antibody-mediated rejection in 5 patients).…”
Section: Patients' Characteristicsmentioning
confidence: 99%
“…4 However, these results may be equivocal because the Everolimus (Certican ® ) Initiation and Calcineurin Inhibitor Withdrawal in Maintenance Heart Transplant Recipients with Renal Insufficiency study examined renal insufficiency patients on maintenance CNI therapy randomized to CNI-free (EVR + mycophenolate mofetil) or standard CNI therapy and did not observe significant renal function improvement in the intention-totreat analysis, but was significant by on-treatment analysis-those who tolerated EVR. 5 High EVR discontinuation rates from adverse reactions (96.6% vs 57.1%, P < .001) may have contributed. 5 Despite their important long-term benefits, high acute rejection rates may limit incorporation of mTORi into CNI-free regimens, especially in the early posttransplant period, but further clinical investigation may clarify and enhance their role.…”
Section: Mtor Inhibitors Vs Calcineurin Inhibitors: a Catch-22preventing Nephrotoxicity Or Acute Allograft Rejection After Heart Transplamentioning
confidence: 98%
“…5 High EVR discontinuation rates from adverse reactions (96.6% vs 57.1%, P < .001) may have contributed. 5 Despite their important long-term benefits, high acute rejection rates may limit incorporation of mTORi into CNI-free regimens, especially in the early posttransplant period, but further clinical investigation may clarify and enhance their role. In MANDELA, acute rejection was almost 3 times higher within the CNI-free arm in the setting of subtherapeutic EVR levels (<5 ng/mL).…”
Section: Mtor Inhibitors Vs Calcineurin Inhibitors: a Catch-22preventing Nephrotoxicity Or Acute Allograft Rejection After Heart Transplamentioning
confidence: 98%
“…39 Other studies have shown that PSIs without CNI are safe and effective in select patients. [40][41][42] While combination therapy appears to be safe and effective, more data are needed to determine whether PSIs can be used as monotherapy.…”
Section: Outcomes Datamentioning
confidence: 99%